Does multisensory stimulation with virtual reality (VR) and smell improve learning? An educational experience in recall and creativity - Andonova, Veneta; Reinoso-Carvalho, Felipe; Jimenez Ramirez, Manuel Arturo; Carrasquilla, David (Frontiers in Psychology, 2023)
The purpose of this study is to derive practical recommendations from multisensory stimulation with virtual reality and scent, to support educators develop effective teaching strategies geared towards aspects of the learning experience, recall, and creativity in a stereotypical learning context. To this end, a randomized experiment was conducted where participants were subdivided into three treatment groups, and one control group. Each group was stimulated by a different combination of visual, auditory, and olfactory stimuli (2D/control, 2D + scent, VR, VR + scent). Traditional video content alone and bundled with a coherent olfactory stimulus prompted higher self-reported ratings of perceived quality of the sensory experience. Olfactory stimulus in combination with either VR or a traditional video prompted higher self-reported ratings on perceived immersion. In a stereotypical learning context the highest recall scores were achieved with traditional video alone. Both VR alone and bundled with an olfactory stimulus resulted in enhanced creativity. The discussion reported in this study intends to offer practical recommendations for instructional design strategies aiming to create multisensory stimulations with VR, and olfactory components, to foster a richer learning experience and enhanced learning outcomes under the assumptions of a stereotypical learning context.